Interacções em fóruns de discussão com alunos do ensino secundário: uma análise sociométrica - Lima, Luísa (2011)
This work applies the methodology of social network analysis to discussion forums that took place in a virtual environment. These forums were implemented within a virtual classroom created in a Web 2.0 platform (http://www.edu20.org). The study was carried out over four months with an English class of secondary school students (11th grade). In this study, the virtual environment worked as a complement to face-to-face learning. The analysis of all the interactions in the forums was done using the software UCINET and NETDRAW. The sociograms that resulted from this analysis show the interactive dynamics, the roles of the different actors and that will allow the teacher to decide his teaching practice accordingly.